Life satisfaction is the most significant determinant of quality of life in the elderly - Vinsalia, Thania; Handajani, Yvonne Suzy (Universa Medicina, 2021)
BackgroundQuality of life tends to decrease as age increases. This study aimed to determine the most significant risk factors (family support, spirituality, and life satisfaction) for the elderly’s quality of life. MethodsThis was a cross-sectional study of 101 subjects aged ³60 years in West Jakarta. The variables were assessed using the World Health Organization Quality of Life–BREF (WHOQOL–BREF), Family Support, Daily Spiritual Experience Scale (DSES), and the Satisfaction with Life Scale (SWLS) instruments. Multivariate logistic regression was used to analyze the association between quality of life and its determinant factors.ResultsBased on sociodemographic characteristics, the respondents were mostly women (66.3%), had more than nine years of education (79.2%), and were married (56.4%). The analysis showed that life satisfaction was significantly associated with overall quality of life (OR=9.71; 95% CI:2.04–46.26; p=0.004) and general health (OR=7.52; 95% CI:1.70–33.25; p=0.008). Life satisfaction was also a risk factor for the environmental domain (OR=36.02; 95% CI:5.07–255.82; p<0.001). Furthermore, spirituality was found to be a risk factor for the physical health domain (OR=4.18; 95% CI:1.51–11.59; p=0.006), psychological domain (OR=6.67; 95% CI:2.4–17.86; p<0.001), and environmental domain (OR=11.46; 95% CI:3.10–42.37; p<0.001).ConclusionLife satisfaction plays a significant role in increasing the environmental domain of quality of life, the overall quality of life, and general health among the elderly. Awareness of these factors can assist providers in identifying people at risk and guide new intervention programs to improve care for these invaluable elderly of our communities.